The Risk of Adverse Pregnancy Outcomes Following Nonobstetric Surgery During Pregnancy: Estimates From a Retrospective Cohort Study of 6.5 Million Pregnancies. Issue 2 (August 2017) - Balinskaite, Violeta; Bottle, Alex; Sodhi, Vinnie; Rivers, Angus; Bennett, Phillip R.; Brett, Stephen J.; Aylin, Paul
Abstract : Objective: The aim of this study was to estimate the risk of adverse birth outcomes for women who underwent nonobstetric surgery during pregnancy compared with those who did not. Background: Previous research suggests that nonobstetric surgery occurs during 1% to 2% of pregnancies. However, there is limited evidence quantifying risks to the mother or pregnancy of such surgery. Methods: We examined maternity admissions using hospital administrative data collected between April 1, 2002, and March 31, 2012, and identified pregnancies wherein nonobstetric surgery occurred. We used logistic regression models to determine the adjusted relative risk, attributable risk, and number needed to harm of nonobstetric surgical procedures for adverse birth outcomes. Results: We identified 6, 486, 280 pregnancies. In 47, 628 of these pregnancies, nonobstetric surgery had occurred. We found that nonobstetric surgery during pregnancy was associated with a higher risk of adverse birth outcomes, although the attributable risk was generally low. We estimated that every 287 surgical operations were associated with 1 additional stillbirth, every 31 operations associated with 1 additional preterm delivery, every 39 operations associated with 1 additional low birth weight baby, every 25 operations associated with 1 additional caesarean section, and every 50 operations associated with 1 additional long inpatient stay. Conclusions: Although we have no means of disentangling the effect of the surgery from the effect of the underlying condition, we found that the risk associated with nonobstetric surgery was relatively low, confirming that surgical procedures during pregnancy are generally safe. We believe that our findings improve upon previous research, and are useful reference points for any discussion of risk with prospective patients. Abstract : Supplemental Digital Content is available in the text